Kinematics of the upward jumping throw in handball - comperison of players with different level of performance - Wagner, H.; Klous, M.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to compare the kinematics and the ball velocity of the upward jumping throw in handball of three groups with different level of performance. Significant differences between the groups were founded for the ball velocity, the segment velocity of the finger and wrist, the angle range of the shoulder flexion and extension and the maximal angular velocity of the shoulder flexion, extension and internal rotation, the elbow flexion and the ulnar deviation of the wrist. Therefore the main caused of an increased ball velocity seems to be an increasing of the angular velocity of the shoulder, especially the shoulder flexion, the elbow extension and the ulnar deviation of the wrist.